Dependence of sensitivity on granulometry in conductimetric γ´-Bi2MoO6 sensors - Vera, C. M. C. (2005)
The sensitivity to ethanol, in O2 /N2 carrier gas, of γ´-Bi2 MoO6 sintered pellets of 10 µm average grain size, is compared with that of thin films, obtained by thermal oxidation of magnetron sputtered, stoichiometrically layered Bi-Mo deposits, with an average grain size of 0.5 µm. Pellet response to a 1.3 % w/w ethanol stimulus, at 500 °C, is 47 %, quantitatively accounted by an increase in ionic conductivity, as evaluated by impedance spectroscopy. This response is totally absent in thin films, under the same conditions, due the increase in electronic and surface conductions.